Sleep disorders and attention: a systematic review - RODRIGUES, Thiago; SHIGAEFF, Nadia (Arquivos de Neuro-Psiquiatria, 2022)
Background: Sleep is a special physiological state that occurs cyclically. The probable role of sleep in our organic functions remains to be explored to clarify the impact of sleep on brain functions. Sleep deprivation is known to affect all parts of the brain separately and independently, but further research is needed on the impact of sleep disorders on attention, particularly the specific types of attention that are most affected, and whether there is such a correlation. Objective: To conduct a systematic review of the possible correlation between sleep disorders and attentional performance. Methods: A systematic review and search at PubMed, SciELO, and Cochrane scientific databases for articles published in the last 10 years was carried out using the following keywords: sleep, attention, and attentional performance. Inclusion criteria were the use of attention tests and sleep disorders. Of the 1398 articles found, 15 were selected and included in this review. Results: The number of publications evaluating sleep and sleep disorders has increased, but is still limited. Of all the functions normally assessed, patients with sleep disorders perform worse on attention tasks, especially with sustained attention. However, these data require further investigation due to the complexity and diversity of the disorders, the small sample size of the included studies, and the fact that few studies used standardized tests. Conclusions: Our findings indicate that the correlation between sleep and attention is strong but limited. Few studies are devoted exclusively to the extent to which sleep disorders interferes with attention.
Keywords: Sleep; Sleep Wake Disorders; Attention